Territorial or nomadic? Geo-social determinants of location-based IT use: a study in Pokémon GO - Laato Samuli; Kordyaka Bastian; Islam A.K.M. Najmul; Papangelis Konstantinos; Hamari Juho (Emerald, 2025)
Purpose Location-based games (LBGs) have afforded novel information technology (IT) developments in how people interact with the physical world. Namely, LBGs have spurred a wave of territoriality (i.e. controlling) and exploration (i.e. discovering) of augmented physical space that are driven by different social dynamics related to group formation, social connectivity and altruism. The aim of this study is to investigate this dynamic and how it is further related to the use intensity of location-based IT.
Design/methodology/approach This work presents a structural equation model that connects social dimensions of play to territorial control and exploration, and playing intensity. The model was tested with sychometric data gathered from a global sample of Pokemon GO players (N = 515).
Findings In the tested sample, players' social self-efficacy and altruism were positively associated with team identification. Team identification, in turn, was positively associated with both territorial control and exploration tendency. Territorial control had a significant relationship with playing intensity; however, exploration tendency did not. This implies territorial control is the stronger predictor of playing intensity.
Practical implications The findings suggest that human primal urges to conquer and control geographical territory may surface in the digital reimagination of physical space. LBGs offer opportunities for making use of new forms of play (territorial control and exploration) in motivating locative behaviours.
Originality/value This research quantifies the relationships between a social predisposition, team identification, territorial control, exploration tendency and playing intensity in the context of Pokemon GO. It contributes new knowledge to the understanding of territorial behaviour (control and exploration) in location-based IT.